The imagination of eco-disaster : post-disaster rebuilding in Asian cinema - Chu, Kiu-Wai (2021)
Commercial films today often reduce representations of natural catastrophes to commodified spectacles that de-contextualize the subject matter. To contemporary film viewers, the ‘psychic numbing’ effect is apparent, and it does not apply merely to our perception of numbers, statistics, the big data. It can also be seen when we are bombarded with similar kinds of images over and over again; in this case, the large-scale tsunami, the hurricanes, the earthquake and all the exaggerated destruction scenes in recent disaster movies have become clichés no matter how realistic and intense the shots are made. By focusing on a range of eco-disaster films, this article highlights the importance of cultural sensitivity in the study of eco-disaster films, by exploring several questions: how are eco-disasters culturally shaped and defined, via cinematic means? How are human responses to disasters, as reflected in cinematic representations, shaped by specific sociopolitical, cultural or economic conditions? How does cinema as a media form represent ecological concepts that are shared globally or universally, while at the same time reflecting specific cultural characteristics? Juxtaposing examples from China, Thailand and the Phillippines, particularly with three films: Wonderful Town (Thailand, 2007), Aftershock (China, 2010) and Taklub (Phillippines, 2015), this article demonstrates how Asian eco-disaster films in the Anthropocene epoch reflect specific cultural imaginations of nation and identity rebuilding, which in turn provide a ground to reposition, redefine and reinvent the changing cultural identities in contemporary Asia. Eventually, it argues that eco-disaster narratives in Asia reflect the identity crisis of Asian nations in a global capitalist world, just as much as they are about ecological crises.